Internalization of Islamic Values at SMK Negeri 8 Surakarta - Aziz, Ridlo Nur; Ali, Mohamad (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
Art schools emphasize creativity and freedom of expression; therefore, they require specific strategies to internalize religious values in order to achieve a balance between art and Islamic morality. This study aims to describe the forms of internalization of Islamic values at SMK Negeri 8 Surakarta and to identify challenges in their implementation. This research employs a qualitative approach using observation and field practice methods. The findings show that the internalization of Islamic values is carried out through religious habituations and activities, such as religious literacy, Qur’anic recitation before Islamic Religious Education lessons, Friday sermon training, Islamic-themed wayang performances, and the habituation of praying for deceased members of the school community. These activities contribute to the development of students’ religious character and social awareness, although challenges remain in the form of low student interest and limited participation in Islamic Religious Education.